The effect of online socialization towards academic performance among bachelor of science in library and information management (Hons) students in UiTM Kedah / Mohd Amienashrof Azaq'iem Che Aziz - Che Aziz, Mohd Amienashrof Azaq'iem (Faculty of Information Management, 2012)
The research was undertaken to investigate the effect of online socialization towards academic performance among Bachelor of Science in Library and Information Management Student in UiTM Kedah. The instrument for the study was a set of questionnaires that was distributed to 144 of IM224 students. It consists of one dependent variable and three independent variables for this research. The dependent variable is academic performance while independent variables are self-efficacy, attitude, and interaction. From the analysis, majority of the students agreed that confident is very important. Therefore, it shows that students think confident is necessary when sharing valuable information with other. The study also showed that students feel happier with the assessment that uses online environment. Other than that, students feel more connected with their friend via online environment. This behaviour can affect their academic performance either in bad way or a good way.